(13)C-octanoic acid breath test (OBT) with a new test meal (EXPIROGer): Toward standardization for testing gastric emptying of solids - Perri, Francesco; Bellini, Massimo; Portincasa, Piero; Parodi, Andrea; Bonazzi, Patrizia; Marzio, Leonardo; Galeazzi, Francesca; Usai, Paolo; Citrino, Attilio; Usai-Satta, Paolo (Digestive and liver disease, 2010)
Standardization of the (13)C-octanoic acid breath test is still lacking. To evaluate the accuracy of the (13)C-octanoic acid breath test using a new standardized ready-to-eat, gluten-, glucose-, and lactose-free muffin. Healthy subjects were recruited and sorted by sex and age. Patients with diabetic gastroparesis and untreated celiac disease with known gastric motility disorders were also tested with the new labelled muffin. Expired breath (13)CO(2) was analysed and t(1/2) was calculated. Overall, 131 healthy subjects were enrolled. The reference range of t(1/2) was 88+/-29min with the value of 146min as the upper limit of normal range. No significant difference in t(1/2) was found among subjects sorted by sex or age. The within-subject variability of t(1/2) was 17%. Mean (+/-standard deviation) t(1/2) values were 179+/-50min in patients with diabetic gastroparesis (n=8) and 151+/-20min in those with untreated celiac disease (n=11) (p<or=0.001 vs controls). A new standardized test meal simplifies the execution of the (13)C-octanoic acid breath test, is not influenced by sex or age, has low intra-individual variability, is palatable, does not cause side effects, and is able to evaluate gastric emptying in both patients and healthy controls. Moreover, it can be used in subjects with lactose intolerance, diabetes, and celiac disease.